Asic design of a kohonen neural network microchip - Rajah, Avinash (IEEE, 2004)
This paper discusses the Kohonen neural network (KNN) processor and its KNN computation engine microchip. The ASIC design of the KNN processor adopts a novel implementation approach whereby the computation of the KNN algorithm is performed on the custom ASIC microchip and its operations are governed by a FPGA based controller. Thus, the ASIC implementation of the KNN processor is derived through integration between a custom ASIC and FPGA. The 3.3V AMI 0.5um CO5M-D process technology was used to achieve the VLSI design of the computation engine microchip and the entire design adopted the BBX cell based methodology, which is a viable alternative to conventional ASIC methodology.